2012
DOI: 10.1007/s40266-012-0016-1
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Prescribing and Related Hospital Admissions in Frail Older Persons According to the STOPP and START Criteria

Abstract: Using the STOPP and START criteria, it was found that inappropriate prescribing events (both PIMs and PPOs) were frequent and were associated with a substantial number of acute hospital admissions in frail older persons. Fall-induced osteoporotic fracture was the most important cause of hospital admission related to inappropriate prescribing and should be a priority for pharmacological optimization approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
112
3
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(135 citation statements)
references
References 39 publications
8
112
3
12
Order By: Relevance
“…15,16 It was as high as 51% in a study conducted by Delleur. 17 A study conducted by Gallenger reports the proportion on PIMs to be between 12-40% and the results of the present study falls between the same range. 18 Thus, studies conducted all over the world on geriatric patients have shown wide variations with respect to this parameter.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…15,16 It was as high as 51% in a study conducted by Delleur. 17 A study conducted by Gallenger reports the proportion on PIMs to be between 12-40% and the results of the present study falls between the same range. 18 Thus, studies conducted all over the world on geriatric patients have shown wide variations with respect to this parameter.…”
Section: Discussionsupporting
confidence: 79%
“…Study published in European Journal of pharmacology shows prescription of NSAIDs in patients of hypertension as a common PIM while studies analyzing prescriptions as per Beers criteria show common PIMs related to prescription of antihistaminic, muscle relaxants and long acting benzodiazepines . [16][17][18][19] Thus, criteria adopted for identification of PIMs play a very important role in explaining the discrepancies between studies in this regard. Other explanations for differences in the type of PIPs reported from studies conducted in different geographical areas may be related to the epidemiology of diseases treated in a particular area, local availability of drugs, cost and treatments guidelines followed in a particular setup.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them were discharged and went home. In our study, polypharmacy was higher than that described in other studies focusing on patients' medicine consumption on hospital admission [11,13,28]. However, an exhaustive pharmacology anamnesis study was carried out in our study analysing the consumption of drugs the month before admission, not only at the time of admission, as well as a complete review of drug utilization from the primary care and hospital electronic medical records, and performing an exhaustive drug interview of patients and/or relatives.…”
Section: Discussionmentioning
confidence: 75%
“…Existe abundante bibliografía sobre estudios de detección de PPI en pacientes hospitalarios [5][6][7], en residencias sociosanitarias y, en menor medida, en atención primaria. Más allá de algunos estudios descriptivos [8,9] hay poca bibliografía publicada en farmacia comunitaria.…”
Section: Introductionunclassified